Species differences in the morphology of transverse tubule openings in cardiomyocytes. (23rd November 2018) - Rog-Zielinska, Eva Alicja; Kong, Cherrie Hei Ting; Zgierski-Johnston, Callum Michael; Verkade, Paul; Mantell, Judith; Cannell, Mark Bryden; Kohl, Peter
Abstract: Aims: The ultrastructure of ventricular cardiomyocyte T-tubule connections with the outer cell surface ('mouth' regions) has been reported to differ between mice and rabbits. In mice, T-tubule mouths form convoluted narrow spaces filled with electron-dense matter that impedes diffusion between T-tubular lumen and bulk extracellular space. Here, we explore whether T-tubule mouths are also constricted in rat (another murine model used frequently for cardiac research) and whether pig and human T-tubule mouth configurations are structurally more similar to mice or rabbits. Methods and results: We used chemically-fixed tissue and high-pressure frozen isolated cardiomyocytes to compare T-tubule mouth architecture using transmission electron microscopy and three-dimensional electron tomography. We find that rat T-tubular mouth architecture is more similar to that of rabbits than mice, lacking the marked tortuosity and electron-dense ground substance that obstructs access to deeper portions of the T-tubular system in mice. Pilot observations in larger mammals (pig, human) suggest that mouse may be the least representative animal model of T-tubule connectivity with the outer cell surface in larger mammals. Conclusion: Rat T-tubular system architecture appears to be more similar in size and topology to larger mammals than mice. T-tubular mouth topology may contribute to differences in experimental model behaviour, underscoring the challenge of appropriate model selection for research into cell and tissue function.